PELATIHAN STUDI KELAYAKAN USAHA AGRIBISNIS UNTUK MENINGKATKAN KEUNTUNGAN PETANI - Ester Dorina Leatemia; Natelda Rosaldiah Timisela; Esther Kembauw (Universitas Islam Malang, 2023)
Farmers in Kamal Village, in running their farming business, are still constrained by various weaknesses in terms of capital, management, marketing, and production aspects. These weaknesses are the main problems faced by farmers in running their farming. The purpose of conducting agribusiness feasibility study training is to be able to provide input regarding targets or achievements that must be realized to maintain the established business so that it can run and develop as desired. This is important so that farmers in Kamal Village can find out whether the farming they have been doing so far can continue to grow and become a profitable business, not just to meet family needs. The method used in community service activities goes through three stages, namely socialization, training, and assistance to farmers who run agribusiness businesses, both vegetable crops, food crops, and fruit crops. The result of this service is to provide farmers with an understanding of the agribusiness feasibility study. The implication of this service activity is that farmers it conducting business pay attention to the feasibility of the business carried out based on the four aspects of business feasibility, if the business being run is not profitable, farmers must think of other business strategies to avoid losses.